Leveraging momentum clustering and PID control for enhanced portfolio management - Ameiy Acharya; Saket Gupta; Krishna Kumba; Patri Upender (Cogent Economics & Finance)
Efficient wealth management in dynamic financial environments is crucial for maximizing returns and mitigating risk. Therefore, this study presents an adaptive portfolio management strategy that combines momentum-based clustering, a Proportional-Integration-Derivative (PID) controller, and efficient frontier (EF) analysis to construct optimal portfolios in dynamic financial environments. A novel integration of a PID controller dynamically adjusts the asset weights to address the limitations of static optimization methods. EF analysis is then employed to identify portfolios with optimal risk-return trade-offs. Our dynamic strategy demonstrates competitive performance compared to conventional benchmarks. From 2017 to 2023, the approach yielded a cumulative return of 135.5%, surpassing Standard and Poor’s 500 (46.66%), Russell’s 2000 Index (11.47%) and NASDAQ (67.88%). These findings suggest that the integration of clustering techniques and PID controllers offers a promising approach for portfolio management.